Unveiling the pyrolysis mechanisms of cellulose: Experimental and theoretical studies. (March 2020) - Yang, Xiaoxiao; Fu, Zewu; Han, Duoduo; Zhao, Yuying; Li, Rui; Wu, Yulong
Abstract: Biomass pyrolysis is a renewable technology for the production of bio-oil and chemicals. The present study aims to develop a fundamental and plausible model for cellulose pyrolysis. The product formation characteristics of cellulose pyrolysis were investigated via Py-GC/MS and TGA-FTIR spectroscopy. The density functional theory method was employed to calculate the energy barriers of different pathways, and the formation and interaction mechanisms of the three most abundant components, levoglucosan, hydroxyacetaldehyde, and pyruvaldehyde, were compared. Levoglucosan is most likely formed via a concerted mechanism; hydroxyacetaldehyde can be formed from C1-C2 and C5-C6 via a ring-opening reaction and dehydration, while pyruvaldehyde is produced via ring opening, followed by dehydration and retro-aldol reactions. Related to the variations in products, the formation of hydroxyacetaldehyde and pyruvaldehyde was suggested to compete with that of levoglucosan. Based on the experimental and theoretical results, a plausible reaction scheme was proposed. By accounting for these main reactions, approximately 80% (in relative area) of the products of cellulose pyrolysis were included. This investigation is crucial to downstream process development for biomass and provides guidance for product control. Highlights: Py-GC/MS and TGA-FTIR were conducted on cellulose pyrolysis. The DFT study was employed to investigate the reaction routes. The formation and interaction mechanism of main products were investigated.